Surgical Techniques for Abdominoperineal Resection for Rectal Cancer: One Size Does Not Fit All - Wilkins, Simon; Yap, Raymond; Mendis, Shehara; Carne, Peter; McMurrick, Paul J. (Frontiers in Surgery, 2022)
Abdominoperineal resection (APR) of rectal cancer is associated with poorer oncological outcomes than anterior resection. This may be due to higher rates of intra-operative perforation (IOP) and circumferential resection margin (CRM) involvement causing higher recurrence rates and surgical complications. To address these concerns, several centres advocated a change in technique from a standard APR to a more radical extralevator abdominoperineal excision (ELAPE). Initial reports showed that ELAPE reduced IOP rates and CRM involvement but increased wound complications and longer surgical duration. However, many of these studies had unacceptable rates of IOP and CRM before retraining in ELAPE. This may indicate that it was a sub-optimal surgical technique, which improved upon training, that had influenced the high CRM and IOP rates rather than the technique itself. Subsequent studies demonstrated that the CRM involvement rate for ELAPE was not always lower than for standard APR and, in some cases, significantly higher. The morbidity of ELAPE can be high, with studies reporting higher adverse events than APR, especially in terms of wound complications from the larger perineal incision required in ELAPE. Whether ELAPE improves short- or long-term oncological outcomes for patients has not been clearly demonstrated. The authors propose that all centres performing rectal cancer surgery audit surgical outcomes of patients undergoing APR or ELAPE and examine CRM involvement, IOP rates, and local recurrence rates, preferably through a national body. If rates of adverse technical or oncological outcomes exceed acceptable levels, then retraining in the appropriate surgical techniques may be indicated.